STRATEGI KEPALA SEKOLAH DAN IMPLEMENTASINYA DALAM PENINGKATAN KOMPETENSI GURU - Kusen, Kusen; Hidayat, Rahmad; Fathurrochman, Irwan; Hamengkubuwono, Hamengkubuwono (Idaarah: Jurnal Manajemen Pendidikan, 2019)
The main problem facing education today is the quality of human resources are low and not sanggupnya follow the progress of science and technology in the era of globalization, where competition quality menajdi something very urgent met by the school, then you need to do is improve the quality of human resources, both from the aspect of intellectual, spiritual, creativity, morality, and responsibility. This study aims to determines how the principal strategy in improving the competence of teachers in terms of pedagogical, professional, personal and social. This study uses qualitative descriptive approach. It can be concluded that the principal strategy in improving the competence of teachers through empowerment by education supervisors.